Depletion of functional ribosomal RNA operons in Escherichia coli causes increased expression of the remaining intact copies. - Condon, C (1993)
The synthesis of ribosomal RNA is a complex and highly regulated process. To study this process, we have used deletion-insertions to disrupt sequentially from one to four of the seven rRNA (rrn) operons on the Escherichia coli genome. Inactivation of four rrn operons caused a 2.3-fold increase in the expression of a chloramphenicol acetyl transferase reporter gene fused to the tandem promoters of rrnA and a similar increase in the expression of the trp tRNA gene at the end of rrnC. This reflected enhanced expression of the remaining operons to compensate for having only three intact copies. The elevated expression was caused by an increase in both transcription initiation and RNA polymerase elongation rates specifically on rrn operons and occurred in the absence of changes in the intracellular concentration of ppGpp, suggesting that ppGpp is not involved in the regulation of this phenomenon. We discuss these results in relation to the ribosome feedback inhibition model described by Nomura and coworkers.